2007
DOI: 10.1038/sj.jp.7211889
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and nutritional factors associated with prolonged cholestatic jaundice in the premature infant

Abstract: Objective: The primary aim of this study was to determine if an association exists between amino-acid levels and development of cholestasis. The secondary aim of our amino-acid dose comparison trial was to identify factors associated with the development of prolonged cholestatic jaundice.Study Design: We compared demographic characteristics and amino-acid levels in neonates who developed cholestasis with those who did not. Parenteral-associated cholestatic liver disease was defined as a direct serum bilirubin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 37 publications
(38 reference statements)
3
42
1
Order By: Relevance
“…Higher dextrose intake also increased the prevalence of cholestasis (68)(69)(70). High cumulative infusion of amino acids may be associated with development of IFALD in children, although a definitive relation has not been demonstrated.…”
Section: Amino Acidsmentioning
confidence: 95%
“…Higher dextrose intake also increased the prevalence of cholestasis (68)(69)(70). High cumulative infusion of amino acids may be associated with development of IFALD in children, although a definitive relation has not been demonstrated.…”
Section: Amino Acidsmentioning
confidence: 95%
“…Steinbach et al [56] examined factors associated with PN administration that may be associated with the development of cholestasis in a cohort of 122 neonates on PN. The authors found that neonates developing PNAC were exposed to PN for a longer period of time, received a higher dose of parenteral amino acids, and were less often on enteral nutrition by the seventh day of life.…”
Section: What Is the Evidence That A Combination Of Lipid Types Resulmentioning
confidence: 98%
“…89 Most of the data on children have been derived from studies of hospitalized premature or newborn infants. An increased risk of IF/PNALD was associated with young gestational age, 90 91,103 An appropriate PN regimen is also important as high parenteral energy intake, 88,95,104 use of a soybean-based lipid emulsion at a dose of >1 g/kg, 53 dextrose infusion >7 mg/ kg/min, 84,105 high amino acid load in premature infants, 90 as well as deficiency of transsulfuration pathway products, most notably choline, 106 have been reported to favour the development of IF/ PNALD. The use of lipid emulsion with a low content of omega-6 fatty acids is recommended both in preventing and treating IF/ PNALD.…”
Section: Patient Populationmentioning
confidence: 99%